MENINGKATKAN KEMAMPUAN KANJI MAHASISWA MELALUI MEDIA KARTU HURUF KANJI - Dyah Prasetiani; Lispridona Diner (Universitas Diponegoro, 2014)
AbstractJapanese character Kanji is difficult for the students who learn Japanese as a foreign language. Bacause Kanji has stroke order, and also Chinese and Japanese ways of reading. Moreover one character of kanji is presenting one meaning, thus the amount of kanji is massive. The informal interview conduct in some students on Semarang State University, Japanese Department, 2nd semester, reveal that students got problems in memorizing the meaning and also the ways of reading and writing kanji. They often find difficulties while combining two kanji characters become a word (jukugo). Some words they didn’t familiar with will cause any further problems such as they didn’t know how to apply it into the sentence. Actually, the text book they use has reading and writing practice sections which is enough and proper to learn by themselves. But sometimes students need to make they own sentences in order to make their memory of kanji more lasting. Since the students admitted that they lacks of practice making sentences, therefore, we conducted an experiment in a class, using kanji card in order to overcome the student’s problems mentioned above. The result shows that this technique is effective and encourages students to: produce jukugo, produce sentences which using the kanji, students feel fun in learning kanji. But, not quite suitable if we conduct it in a large class.